Adolescents have not been well served by responses to the pandemic and the climate crisis. (1st November 2021) - Costello, Anthony; Clark, Helen; Kobia, Margaret; Martinez, Julieta
Abstract : Tackling climate change and the pandemic are necessary to regain their trust